Paradoks Kebijakan Efisiensi Prabowo - Muhnizar Siagian, Muhnizar Siagian; Rafisa Rona Dillaputri, Rafisa Rona Dillaputri; Calyaretta Meiskha Wanodya, Calyaretta Meiskha Wanodya; Muhammad Chanif Hidayat, Muhammad Chanif Hidayat; Everd S.R Daniel, Everd S.R Daniel (JOURNAL OF GOVERNMENT SCIENCE, 2025)
Abstract: After his inauguration as the 8th President of Indonesia, President Prabowo decided to increase the number of ministers, deputy ministers, and ministerial-level officials. Under Prabowo’s administration, there are 48 ministries, a significant increase compared to the previous government. Naturally, this expansion corresponds to a larger state budget allocation to support ministerial performance. However, through Presidential Instruction No. 1 of 2025, President Prabowo mandated budget efficiency in state and regional expenditures (APBN-APBD) for 2025. Though some remain unaffected, several ministries and state agencies have reduced their budgets in response to this instruction. This situation underscores an apparent inconsistency between these two early policies of Prabowo’s administration. This study aims to analyze this inconsistency using a qualitative case study approach. The findings indicate that although President Prabowo’s policies appear contradictory, they are driven by specific motives, namely accommodative-compromising interests and transactional politics in the expansion of ministries, as well as the need to allocate a substantial portion of the budget to his populist initiative: the free nutritious meal initiative. Keywords: Prabowo, Cabinet, Efficiency, Inconsistency, Paradox